2010
DOI: 10.1111/j.1743-6109.2010.02062.x
|View full text |Cite
|
Sign up to set email alerts
|

Summary of the Recommendations on Sexual Dysfunctions in Men

Abstract: Introduction Sexual health is an integral part of overall health. Sexual dysfunction can have a major impact on quality of life and psychosocial and emotional well-being. Aim To provide evidence-based, expert-opinion consensus guidelines for clinical management of sexual dysfunction in men. Methods An international consultation collaborating with major urolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
260
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 450 publications
(293 citation statements)
references
References 3 publications
2
260
0
10
Order By: Relevance
“…[3] This sexual history allows the healthcare provider to: (i) confirm the patient's diagnosis; (ii) evaluate the impact of the distress on the patient's overall health; and (iii) set management goals. When used in combination with a medical history focused particularly on cardiovascular, neurological, urogenital, hormonal and psychological systems, the sexual history provides indicators of aetiology, while establishing comorbid medical conditions and their potential role in sexual dysfunction.…”
Section: International Classification Of Diseases and Related Health mentioning
confidence: 99%
“…[3] This sexual history allows the healthcare provider to: (i) confirm the patient's diagnosis; (ii) evaluate the impact of the distress on the patient's overall health; and (iii) set management goals. When used in combination with a medical history focused particularly on cardiovascular, neurological, urogenital, hormonal and psychological systems, the sexual history provides indicators of aetiology, while establishing comorbid medical conditions and their potential role in sexual dysfunction.…”
Section: International Classification Of Diseases and Related Health mentioning
confidence: 99%
“…A Chinese epidemiological survey in 2010 revealed that the total prevalence rate of diabetes was up by 9.7% (1). Erectile dysfunction (ED) is sexual dysfunction characterized by the inability to develop or maintain an erection of the penis during sexual activity over the course of three months (2), and is one of the chronic complications in males with type 2 diabetes. Numerous studies have reported that the incidence of ED in diabetic individuals varies between 30 and 80%, which is six times higher compared with normal individuals, and augments with an increase in age and duration of diabetes (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have estimated it to afflict 0.15-11% of men (Nathan, 1986;Spector & Carey, 1990;Laumann et al, 1999;Rowland et al, 2004). DE has been associated with anxiety, depression, shame, performance anxiety, relationship distress, sexual dissatisfaction, low self-esteem and selfimage, intimacy avoidance and relationship dissatisfaction (Masters & Johnson, 1970;Jannini et al, 2002a,b;Montorsi et al, 2010;Abdel-Hamid & el Saleh, 2011;Mulhall & Hsiao, 2014).…”
Section: Introductionmentioning
confidence: 99%